ANALISIS PERBANDINGAN UTILITAS DAN PERILAKU PEMANFAATAN PELICAN CROSSING DI AREA UNIVERSITAS BRAWIJAYA - Ratih Ardia Sari; Remba Yanuar Efranto; Amanda Nur Cahyawati (Journal of Engineering and Management in Industrial System, 2016)
Pelican Crossing is one of  facilities that available in Malang City for pedestrians. Although it had been provided, pedestrians sometimes donot utilize this pelican crossing. This research would be carried out a comparative analysis of pelican crossing utilization and road user behavior on Veteran and MT Haryono street. Worksampling was used to determine the utilization of pelican crossing. From this study, pelican crossing utilization in Veteran street higher than in MT Haryono street during weekday at 51%. The behavior of road users could be seen in the breakdown of activities undertaken at the time of observation. The behavior of road users tend to be more dicipline in the pelican crossing in MT Haryono compared with Veterans.Percentage of incompatibility used of pelican crossing by road users at Veteran's higher than MT Haryono. Incompatibility use of pelican crossing due to the ignorance of community about crossing facilities, undicipline behavior of road user and malfunction of the pelican crossing